Lack of congruence between terrestrial and epiphytic lichen strata in boreal forests. (January 2021) - Smith, Robert J.; Jovan, Sarah; Will-Wolf, Susan
Abstract: Lichens occupy diverse substrates across tremendous ranges of environmental variation. In boreal forests, lichen communities co-occur in 'strata' defined by terrestrial or arboreal substrates, but these strata may or may not be interchangeable as bioindicators. Do co-occurring lichen strata have similar community structures and environmental responses? Could one stratum serve as a proxy for the other? We assessed variation in species richness and community compositions between ground-layer versus epiphyte-layer lichen strata in boreal forests and peatlands of interior Alaska. Species richness was lower and more spatially structured in the ground layer than the epiphyte layer. Richness of strata was not correlated. The most compositionally unique ground-layer communities were species-poor but contained regionally rare species not common in other plots. Variation in community compositions (ordination scores) were not congruent between strata (Procrustes congruence < 0.16 on 0–1 scale); the largest departures from congruence occurred where ground layers were species-poor. The best predictors of ground-layer community compositions were hydrological and topographic, whereas epiphytes were most associated with macroclimate and tree abundances. We conclude that lichens on different substrates 'move in different circles': compositional gradients did not agree and the environmental gradients most important to each lichen stratum were not the same. The conditions which strongly influence one vegetation stratum may have little bearing upon another. As global changes modify habitats, an incremental change in environment may lead community trajectories to diverge among lichen strata.